Manajemen Strategis Penerimaan Peserta Didik melalui Sinergi Humas dan Kesiswaan pada Pendidikan Anak Usia Dini - Subar Junanto; Mila Faila Shofa; Latifah Permatasari Fajrin (Southeast Asian Journal of Islamic Education Management, 2025)
The management of new student admission (PPDB) is a strategic aspect in ensuring the sustainability of schools, as it determines both the quantity and quality of student intake. The increasing competition between public and private educational institutions requires schools to implement systematic and adaptive PPDB strategies. This study aims to describe the management of PPDB at BA Aisyiyah Mayang, Sukoharjo Regency, in the 2024/2025 academic year through the optimization of the roles of public relations and student affairs. The research employed a descriptive qualitative approach with data collected through observation, interviews, and documentation. The research subjects included the principal, the public relations team, and the student affairs team. The findings reveal that PPDB implementation began with comprehensive planning, including determining student capacity, setting registration requirements, and preparing promotional strategies. The organizational stage involved forming a committee, distributing tasks, and ensuring internal and external coordination. During implementation, the school provided both online and offline registration, conducted student readiness observations, uniform measurements, parent briefings, and the Masa Ta’aruf Siswa Madrasah (Matsama) program. Supervision was carried out at multiple levels by the foundation, principal, and committee through regular meetings, daily reports, and parent satisfaction surveys. The study concludes that the synergy between public relations and student affairs played a crucial role in the success of PPDB, as evidenced by the fulfillment of student admission quotas and the strengthening of the school’s positive public image.